Yishen Qingli Heluo Granule Ameliorates Renal Dysfunction in 5/6 Nephrectomized Rats by Targeting Gut Microbiota and Intestinal Barrier Integrity - Sun, Xian; Chen, Jie; Huang, Yiting; Zhu, Sha; Wang, Shuaishuai; Xu, Zijing; Zhang, Junfeng; Sun, Wei (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) is characterized by imbalanced gut microbiota and impaired intestinal barrier. Hence, efforts to ameliorate renal dysfunction by manipulating gut microbial ecosystem are underway. Yishen Qingli Heluo granule (YQHG) is a representative traditional Chinese medicine (TCM) prescription for clinical treatment of CKD. However, its underlying mechanism has not been well elucidated. This study aimed to explore effects of YQHG on renal dysfunction in 5/6 nephrectomized rats by targeting gut microbiota and intestinal barrier. Here, we found that YQHG provided significant renal protection in 5/6 nephrectomized rats by reducing renal fibrosis and inflammation, reestablishing bacterial communities, and improving intestinal barrier. Our analysis showed that YQHG altered the bacterial community of 5/6 nephrectomized rats. In particular, the prescription significantly increased the relative abundance of SCFA-producing bacteria (i.e. Lactobacillaceae, Lactobacillus and Lactobacillus_gasseri), which was contributed to the improved SCFA concentration (i.e. total SCFA, acetic acid, butyric acid) and intestinal barrier (i.e. the improved permeability and microbial translocation). More critically, microbiota-transfer study showed that the protective effect of YQHG was partly attributed to the mediation of the gut microbiota, especially the SCFA-producing bacteria. Our current findings propose a microbiota-targeted intervention and indicate that YQHG may become a novel promising treatment for CKD.